2013
DOI: 10.1165/rcmb.2013-0013oc
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Overexpression of Receptors for Advanced Glycation End-Products in the Adult Murine Lung Causes Airspace Enlargement and Induces Inflammation

Abstract: Receptors for advanced glycation end-products (RAGE) are multiligand surface receptors detected abundantly in pulmonary tissue. Our previous work revealed increased RAGE expression in cells and lungs exposed to tobacco smoke and RAGE-mediated cytokine expression via proinflammatory mechanisms involving NF-κB. RAGE expression is elevated in various pathological states, including chronic obstructive pulmonary disease; however, precise contributions of RAGE to the progression of emphysema and pulmonary inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…A recent study also revealed that HMGB1 release by airway epithelial cells contributes to pathophysiologic hallmarks of allergic asthma via mechanisms that involve RAGEand TLR4-mediated signaling (68). In the context of COPD and tissue repair, a study by Stogsdil et al (64) reported that conditional overexpression of RAGE in adult murine alveolar epithelia resulted in altered matrix turnover. To our knowledge, our study and those by Pittet et al (49) are unique in demonstrating a role for RAGE in mediating HMGB1-induced intracellular signaling and wound healing in airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also revealed that HMGB1 release by airway epithelial cells contributes to pathophysiologic hallmarks of allergic asthma via mechanisms that involve RAGEand TLR4-mediated signaling (68). In the context of COPD and tissue repair, a study by Stogsdil et al (64) reported that conditional overexpression of RAGE in adult murine alveolar epithelia resulted in altered matrix turnover. To our knowledge, our study and those by Pittet et al (49) are unique in demonstrating a role for RAGE in mediating HMGB1-induced intracellular signaling and wound healing in airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated protein was precisely quantified with a BCA Protein Assay kit (Fisher Scientific), and exactly 20 g of total lung protein was used in blotting. Immunoblotting for RAGE protein using a mouse polyclonal antibody (#AF1179; RnDSystems, Pittsburg, PA) and qPCR for RAGE mRNA were completed as already outlined (39). Band densitometry was performed using Un-Scan-It software (Silk Scientific, Orem, UT) and digitized images of the resulting immunoblots.…”
Section: Methodsmentioning
confidence: 99%
“…Such pathways include those associated with fibroblast growth factors (Fgfs), sonic hedgehog (Shh), bone morphogenetic protein 4 (Bmp4), vascular endothelial growth factors (Vegfs), thyroid transcription factor 1 (TTF-1), and Wnts (Burri, 1984;Cardoso, 2001;Copland and Post, 2004;deMello et al, 1997;Gluck, 1978;Stogsdill et al, 2012;Ten Have-Opbroek, 1991;Torday, 1992). When these or other important genetic pathways are defective or delayed, pulmonary hypoplasia or pulmonary agenesis may occur resulting in abnormally low or absent bronchopulmonary segments and terminal alveoli (Ballard, 1980;Stogsdill et al, 2013).…”
Section: Discussionmentioning
confidence: 99%